1990
DOI: 10.1113/jphysiol.1990.sp018289
|View full text |Cite
|
Sign up to set email alerts
|

Quantal analysis of inhibitory synaptic transmission in the dentate gyrus of rat hippocampal slices: a patch‐clamp study.

Abstract: SUMMARY1. Synaptically connected neurones were identified in the granule cell layer of slices of 17-to 21-day-old rat hippocampus. Whole-cell current recording using the patch-clamp technique revealed synaptic currents ranging from less than 10 to 200 pA in symmetrical Cl-conditions, at a holding potential of -50 mV. These currents were blocked by 2 ftM-bicuculline, indicating that they result from the activation of postsynaptic y-aminobutyric acid receptor (GABAA-receptor) channels.2. Addition of tetrodotoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
323
8
3

Year Published

1994
1994
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 486 publications
(379 citation statements)
references
References 52 publications
(52 reference statements)
45
323
8
3
Order By: Relevance
“…5). Finally, variations in the site of exocytosis of synaptic vesicles relative to the location of postsynaptic glutamate receptors could cause variable amounts of glutamate to be sensed by postsynaptic receptors (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…5). Finally, variations in the site of exocytosis of synaptic vesicles relative to the location of postsynaptic glutamate receptors could cause variable amounts of glutamate to be sensed by postsynaptic receptors (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…We applied a method used by Edwards et al (1990; Asertine's analysis) to diagnose the occurrence of peaks in mIPSC amplitude histograms. The autocorrelation function (ACF) of the amplitude histograms was calculated using the expression: ACF(j) = {$i H(i)H(i+j)}/($i H(i)H(i)), where H(i) is the height of the i th bin which is centred at the amplitude value given by i " bin width.…”
Section: Assessment Of Peaks In the Mipsc Amplitude Distributionmentioning
confidence: 99%
“…In "dinapses" of amacrine cells it has been suggested that GABA A receptors are not saturated, based on the observation that transmitter concentration is the major determinant of mIPSC amplitude (Frerking et al, 1995). On the other hand, the low quantal variance of evoked IPSCs (Edwards et al, 1990), nonstationary fluctuation analysis, and pharmacological approaches support the hypothesis of saturation in hippocampal granule cells (Otis and Mody, 1992;De Koninck and Mody, 1994). Although differences in the anatomy of the synapses, the amount of GABA released in the cleft, and the kinetic properties of the GABA A receptors may generate a variety of scenarios (Frerking and Wilson, 1996), it is clear that more experiments and measurement of cleft GABA concentration during synaptic transmission are needed to resolve this issue.…”
Section: Functional Implicationsmentioning
confidence: 99%